Human ANKLE1 Is a Nuclease Specific for Branched DNA. Issue 21 (2nd October 2020) - Song, Junfang; Freeman, Alasdair D.J.; Knebel, Axel; Gartner, Anton; Lilley, David M.J.
Abstract: All physical connections between sister chromatids must be broken before cells can divide, and eukaryotic cells have evolved multiple ways in which to process branchpoints connecting DNA molecules separated both spatially and temporally. A single DNA link between chromatids has the potential to disrupt cell cycle progression and genome integrity, so it is highly likely that cells require a nuclease that can process remaining unresolved and hemi-resolved DNA junctions and other branched species at the very late stages of mitosis. We argue that ANKLE1 probably serves this function in human cells (LEM-3 in Caenorhabditis elegans ). LEM-3 has previously been shown to be located at the cell mid-body, and we show here that human ANKLE1 is a nuclease that cleaves a range of branched DNA species. It thus has the substrate selectivity consistent with an enzyme required to process a variety of unresolved and hemi-resolved branchpoints in DNA. Our results suggest that ANKLE1 acts as a catch-all enzyme of last resort that allows faithful chromosome segregation and cell division to occur. Graphical abstract: Unlabelled Image Highlights: Human ANKLE1 is a nuclease that cleaves branched DNA. ANKLE1 cleaves a variety of branched DNA species, including four-way junctions, flaps and Y-structures. The activity of ANKLE1 is consistent with a catch-all nuclease to sever links between chromosomes prior to cell division. ANKLE1 is probably the enzyme of last resort processing links between chromosomes.